Some thoughts on dynamic systems modeling of L2 learning - Van Geert, Paul L.C. (Frontiers in Physics, 2023)
I present a highly simplified dynamic systems model of L2 learning. Its basic features are 1) at any moment in time, a learner’s L2 proficiency is a distribution of potentialities (possible levels of L2 production), 2) the distribution changes as a result of experienced L2-events such as conversations, 3) L2 proficiency and L2 events are represented on the same underlying array of linguistic proficiency 4) learning processes are “normative” in the sense that they are governed by an optimum between familiarity and novelty; 5) the parameters governing the systems dynamic differ among individual learners. The model generates typical patterns of variability and combinations of discontinuity and continuity in the learning process described in the empirical literature.